Pertanggungjawaban Terhadap Anggota Tentara Nasional Indonesia Yang Memakai Narkotika Jenis Sabu (Studi Kasus Di Dilmil I – 02 Medan) - Nasution, Nico Saputra; Rahmayanti, Rahmayanti (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
In terms of its position before the law, the Indonesian National Army has the same position as other citizens, meaning that they are equally subject to the provisions of the laws that apply in the country, both civil law, civil procedural law, criminal law and criminal procedural law. However, the Indonesian National Army in regulating criminal law and criminal procedure law has its own legal rules and tools. Thus, members of the TNI as Indonesian citizens are not only subject to the provisions of the military criminal law listed in the Military Criminal Code, Military Court Decisions and even in the awareness of the military community and the life of the military community. What are the factors that cause members of the Indonesian National Army to use methamphetamine-type narcotics, how are efforts applied to members of the Indonesian National Army who are involved in narcotics crimes and how to be held accountable for members of the Indonesian National Army who use methamphetamine-type narcotics. This study uses a type of empirical juridical research through field research. The data collection method used is the library research method and the field research method. Data collection was carried out by interviews. The interview was conducted at Dilmil I-02 Medan. The follow-up for TNI members who have served punishment or criminal sanctions for narcotics cases is after receiving a detention verdict and additional punishment to be fired from military service and handed over to a correctional institution. The TNI leadership is emphatically in fighting drugs with dismissal sanctions for every soldier affected by narcotics cases, dismissal sanctions do not only apply to soldiers who are directly involved in drug cases, but the sanctions also apply to soldiers who know and allow drug trafficking in their areas. The form of criminal responsibility for TNI members who use methamphetamine is imprisonment and additional punishment for dismissal from military service.